Somatic Malignant Transformation of a Testicular Teratoma: A Case Report and an Unusual Presentation. (3rd November 2019) - Ibrahim, Dalia Y.; Sun, Hongliu
Abstract : Testicular cancer represents 1% of all malignant tumors in men. About 95% of testicular cancers are germ cell tumors (GCTs). These can be divided into nonseminomatous GCTs (NSGCTs) and seminomas. NSGCTs include teratomas, yolk sac tumors, embryonal carcinomas, choriocarcinomas, and mixed tumors. Only 2–6% of testicular teratomas are pure teratomas. Pure teratomas can be subdivided into prepubertal and postpubertal. The prognosis is significantly different between these two age groups. Different from teratomas in ovary, the immaturity in a teratoma is not an indication of their biologic behavior; the age of the patient is of greater importance. Malignant transformation of teratoma occurs in only 3–6% of testicular GCTs. The most frequent transformed histologic types consist of rhabdomyosarcoma, adenocarcinoma, and primitive neuroectodermal tumors. We report a rare case of pure postpubertal testicular teratoma with a secondary somatic malignancy that was an incidental finding in a patient presenting with lower back pain and testicular torsion.